Energy performance of rammed earth building: A Kathmandu valley case study - Uprety, Priyanka; Shrestha, Barsha; Uprety, Sanjaya (Journal of Engineering Issues and Solutions, 2024)
As the world’s energy demands soar, the building sector is under pressure to innovate. Rammed earth (RE) construction emerges as a sustainable and efficient alternative that could revolutionize building design. With the right materials, preparation methods, and a focus on energy use efficiency, RE can significantly reduce our reliance on conventional heating and cooling systems by leveraging the natural thermal mass of the walls to maintain a consistent internal temperature year-round. Despite growing interest, particularly in the Kathmandu valley, there is a lack of research on the actual energy performance of RE buildings. This study aims to evaluate the energy performance of RE buildings using thermal imaging and energy simulation to compare RE walls with traditional brick walls. Results indicate that RE buildings perform better, with temperature differences of 2.9°C and 2.1°C in the south and west walls, respectively, as measured by a thermal imager at a distance of 1 meter and a height of 1.5 meters. Furthermore, simulation results reveal that RE construction exhibits the lowest heating and cooling loads, while brick masonry construction shows the highest. These findings suggest that incorporating RE construction can lead to significant energy savings and enhanced thermal comfort in buildings, offering practical applications for sustainable building practices and broader generalizability in similar geographical and climatic contexts.